SIKAP DALAM MENGHADAPI TANTANGAN DAKWAH DI ERA GLOBAL (Analisis Al-Qur’an Surat Ali Imran ayat 159 dan 168) - Achmad Slamet (Fakultas Dakwah dan Komunikasi Program Studi Komunikasi dan Penyiaran Islam, 2022)
People in the era of globalization tend to ignore Islamic morals and values and have a westernized attitude. The attitude of consumerism, secularism, hedonism characterizes this era of globalization. This situation is a problem faced by Muslims. This problem has had a great influence on both Islam and the West in particular. From this context, this study seeks to determine attitudes towards the challenges of da'wah that occur in the era of globalization and how to self-actualize a preacher. The method used in this study is a qualitative research method and uses a model of reviewing books and documents. While the data sources used are primary data sources in the form of the Al-Quran and books of interpretation. The result is that the preacher at least has the attitude that is in the Al-Quran Surah Ali Imran verses 159 and 186 in facing the challenge of da'wah. Among them are gentle, not rude, forgiving, like deliberation, determined, tawakkal, patient and pious. However, to respond to the conditions of the current era of globalization, that is not all that is needed but requires the right concept and strategy of da'wah, maintaining noble cultural values that can preserve positive traditions, needs support and community participation to create the same commitment and readiness and maturity. intellectual mentality of the preachers, coupled with the mastery of science and technology.